THE TERM "TRANSLATION" IN THE ASPECT-COMPLEX PRINCIPLE OF TRAINING STUDENTS OF THE NATIONAL AUDIENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article refers the principles of teaching in the methodology are understood as the initial provisions, which in their totality determine the requirements for the system of language teaching as a whole, and its individual components: for the goals, content, forms, methods and means of teaching.